Motivations for Business Start-up: Are There any Differences Between Disabled and Non-disabled Microfinance Clients? - Leif Atle Beisland; Roy Mersland; Stephen Zamore (Journal of International Development, 2016)
We use an Ecuadorian sample to investigate if there are differences in motivations for business start-up between persons with and without disabilities. Generally, we do not document significant differences. The reason might be that we use a sample selected among customers of the microfinance bank Banco D-MIRO. Without targeted incentives, disabled microfinance customers must resemble non-disabled customers. Copyright 2015 John Wiley & Sons, Ltd.
Keywords: 650